Three Layers of Intestinal γδ T Cells Talk Different Languages With the Microbiota - Rampoldi, Francesca; Prinz, Immo (Frontiers in Immunology, 2022)
The mucosal surfaces of our body are the main contact site where the immune system encounters non-self molecules from food-derived antigens, pathogens, and symbiotic bacteria. γδ T cells are one of the most abundant populations in the gut. Firstly, they include intestinal intraepithelial lymphocytes, which screen and maintain the intestinal barrier integrity in close contact with the epithelium. A second layer of intestinal γδ T cells is found among lamina propria lymphocytes (LPL)s. These γδ LPL are able to produce IL-17 and likely have functional overlap with local Th17 cells and innate lymphoid cells. In addition, a third population of γδ T cells resides within the Peyer´s patches, where it is probably involved in antigen presentation and supports the mucosal humoral immunity. Current obstacles in understanding γδ T cells in the gut include the lack of information on cognate ligands of the γδ TCR and an incomplete understanding of their physiological role. In this review, we summarize and discuss what is known about different subpopulations of γδ T cells in the murine and human gut and we discuss their interactions with the gut microbiota in the context of homeostasis and pathogenic infections.